2000
DOI: 10.1111/j.1744-7429.2000.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Phyllostomid Bat Assemblages in Undisturbed Neotropical Forest and in Forest Fragments of a Slash‐and‐Burn Farming Mosaic in Petén, Guatemala1

Abstract: Using mist nets, we compared phyllostomid bat ensembles of continuous mature forest in Tikal National Park, Guatemala, and of forest fragments in the nearby farming landscape. Of 20 species captured, 13 were shared between treatments, 4 were unique to continuous forest, and 3 were unique to forest fragments. Dominance–diversity curves were similar for the two treatments except that Sturnira lilium comprised 43 percent of captures in the forest fragments, resulting in greater dominance there. Capture rates (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
24

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 39 publications
6
87
2
24
Order By: Relevance
“…Another study surveying coffee shade plantations of Antigua Guatemala reported a lower diversity than our survey with only 12 bat species (Kraker-Castañeda & Pérez-Consuegra 2011). However, two other studies in Guatemala reported higher diversity than our survey, respectively 20 species of Phyllostomidae in forests of the Tikal National Park (Schulze et al 2006) and 42 species in 13 sites across Guatemala (Ubico & McLean 1995). The important specific diversity detected in this last study probably results from the high diversity of habitats sampled.…”
Section: Mist Net Surveyscontrasting
confidence: 63%
“…Another study surveying coffee shade plantations of Antigua Guatemala reported a lower diversity than our survey with only 12 bat species (Kraker-Castañeda & Pérez-Consuegra 2011). However, two other studies in Guatemala reported higher diversity than our survey, respectively 20 species of Phyllostomidae in forests of the Tikal National Park (Schulze et al 2006) and 42 species in 13 sites across Guatemala (Ubico & McLean 1995). The important specific diversity detected in this last study probably results from the high diversity of habitats sampled.…”
Section: Mist Net Surveyscontrasting
confidence: 63%
“…which, in coffee plantations, are frequently weeded out in plantation maintenance. This suggests a strong relationship between Sturnira bats and the understory food items in disturbed cloud forests, as has been reported for tropical semi-deciduous forest fragments (Schulze et al 2000). In the studied region, this relationship is reinforced by the pasture matrix surrounding most forest fragments, which renders other fruit resources unavailable for small bats such as Sturnira.…”
Section: Factors Explaining Bat Abundance Patternsmentioning
confidence: 68%
“…Também foi amplamente amostrado nas outras áreas, perfazendo 62% das coletas no fragmento médio e 32% no fragmento grande. Platyrrhinus lineatus, S. lilium e C. perspicillata representaram 6, 7 e 2,5%, respectivamente, do total de coletas dos pequenos fragmentos, o que sugere serem, também, espécies indicadoras de áreas perturbadas, embora, para C. perspicillata, ao contrário do que preconiza SCHULZE et al (2000), de que é uma espécie indicadora de áreas devastadas, os resultados obtidos neste estudo indicam que sua ocorrência está muito mais relacionada à presença do gênero Piper, sua alimentação preferencial (CHARLES-DOMINIQUE 1991, MARINHO-FILHO 1991, BIZERRIL & RAW 1998, do que ao fato de a área estar degradada ou não, pois durante 10 anos de coletas, na região de Londrina, nunca foi capturada em locais onde não houvesse piperáceas, mesmo que se tratasse de ambiente degradado.…”
Section: Discussionunclassified